Queering desistance: Chrononormativity, afterwardsness and young men’s sexual intimate partner violence - Berggren, Kalle (Criminology & criminal justice, 2020)
Queer criminology has primarily focused on lesbian, gay, bisexual, transgender, and queer people as victims and perpetrators of crime, as well as on the criminalization of non-heterosexual practices. In this article, we contribute to the emerging discussions on how queer theory can be used in relation to criminological research by exploring desistance processes from a queer temporality perspective. Desistance research emphasizes how and why individuals cease offending and is often guided by a teleology in which individuals are expected to mature and develop new, non-criminal identities. Work on queer temporality, in contrast, has developed thinking that destabilizes chronology and troubles normative life trajectories. In this article, we draw on queer temporality perspectives, particularly the concepts of chrononormativity and afterwardsness, in analysing narratives of young men who have used sexual violence against women partners in Sweden. We demonstrate how criminal identities may develop in retrospect, after desisting, and that identity and behaviour may not necessarily go together.